Tubular Lesions Predict Renal Outcome in Antineutrophil Cytoplasmic Antibody-Associated Glomerulonephritis after Rituximab Therapy - Berden, Annelies E.; Waldherr, Rüdiger (Journal of the American Society of Nephrology, 2011)
Histopathological features in renal biopsies of patients with antineutrophil cytoplasmic antibody-associated vasculitis have predictive value for renal outcome in patients who receive standard treatment with cyclophosphamide and corticosteroids; however, whether the same holds true for rituximab-treated patients is unknown. We describe associations between renal histopathology and outcomes among patients treated with a rituximab-based regimen in the Randomized Trial of Rituximab versus Cyclophosphamide in ANCA-Associated Vasculitis trial. Two pathologists, blinded to clinical data, reviewed biopsies from 30 patients according to a standardized protocol that included assessment of T cell, B cell, and plasma cell infiltration, as well as scoring for tubulitis, interstitial inflammation, and glomerulitis. We did not observe associations between immunohistology scores and age, sex, estimated GFR at entry, or requirement for dialysis. However, tubulointerstitial inflammation was more severe among patients who had a positive test for the myeloperoxidase antineutrophil cytoplasmic antibody. In a multiple linear regression model, both CD3+ T cell tubulitis and tubular atrophy independently associated with estimated GFR at 12 months. Tubular atrophy remained an independent predictor at 24 months (P<0.01). These results suggest that in addition to anti-B cell therapy, therapy directed at T cells may improve renal outcomes in antineutrophil cytoplasmic antibody-associated vasculitis.